Gliding-induced ski vibrations: Approaching proper modeling - Koptyug, A.; Bäckström, M.; Tinnsten, M. (Procedia Engineering, 2014)
Phenomena of the ski and snow boards vibrations generated in gliding are known for years. In the cross country and jumping skis such vibrations are not very obvious but can play quite positive role reducing the effective gliding friction. The research into the nature of friction-induced vibrations and the factors influencing their frequencies and magnitudes is driven by the desire to control them for improving ski gliding performance. Significant amount of experimental data acquired in the field and laboratory studies is already available making it possible to formulate certain qualitative conclusions. But so far it did not bring comprehensive understanding of the phenomenon and specifically of the mechanisms controlling such vibrations. Modeling is one of the potent tools allowing to deeper understand experimentally studied phenomena and it can provide much stronger quantitative prediction capacity. Present paper discusses possible approaches to modeling of the phenomenon and first results of constructing simplified models.